DEFINITION arity_gen_bind()
TYPE =
       b:B
         .not (eq B b Abst)
           g:G
                .c:C
                  .u:T
                    .t:T
                      .a2:A
                        .arity g c (THead (Bind b) u t) a2
                          ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2
BODY =
        assume bB
        suppose Hnot (eq B b Abst)
        assume gG
        assume cC
        assume uT
        assume tT
        assume a2A
        suppose H0arity g c (THead (Bind b) u t) a2
           assume yT
           suppose H1arity g c y a2
             we proceed by induction on H1 to prove 
                eq T y (THead (Bind b) u t)
                  ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2
                case arity_sort : c0:C n:nat 
                   the thesis becomes 
                   H2:eq T (TSort n) (THead (Bind b) u t)
                     .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t (ASort O n)
                      suppose H2eq T (TSort n) (THead (Bind b) u t)
                         (H3
                            we proceed by induction on H2 to prove 
                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort True
                                 | TLRef False
                                 | THead   False
                               case refl_equal : 
                                  the thesis becomes 
                                  <λ:T.Prop>
                                    CASE TSort n OF
                                      TSort True
                                    | TLRef False
                                    | THead   False
                                     consider I
                                     we proved True

                                        <λ:T.Prop>
                                          CASE TSort n OF
                                            TSort True
                                          | TLRef False
                                          | THead   False

                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort True
                                 | TLRef False
                                 | THead   False
                         end of H3
                         consider H3
                         we proved 
                            <λ:T.Prop>
                              CASE THead (Bind b) u t OF
                                TSort True
                              | TLRef False
                              | THead   False
                         that is equivalent to False
                         we proceed by induction on the previous result to prove ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t (ASort O n)
                         we proved ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t (ASort O n)

                         H2:eq T (TSort n) (THead (Bind b) u t)
                           .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t (ASort O n)
                case arity_abbr : c0:C d:C u0:T i:nat :getl i c0 (CHead d (Bind Abbr) u0) a:A :arity g d u0 a 
                   the thesis becomes 
                   H5:eq T (TLRef i) (THead (Bind b) u t)
                     .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                   () by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa1:A.arity g d u a1 λ:A.arity g (CHead d (Bind b) u) t a
                      suppose H5eq T (TLRef i) (THead (Bind b) u t)
                         (H6
                            we proceed by induction on H5 to prove 
                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef True
                                 | THead   False
                               case refl_equal : 
                                  the thesis becomes 
                                  <λ:T.Prop>
                                    CASE TLRef i OF
                                      TSort False
                                    | TLRef True
                                    | THead   False
                                     consider I
                                     we proved True

                                        <λ:T.Prop>
                                          CASE TLRef i OF
                                            TSort False
                                          | TLRef True
                                          | THead   False

                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef True
                                 | THead   False
                         end of H6
                         consider H6
                         we proved 
                            <λ:T.Prop>
                              CASE THead (Bind b) u t OF
                                TSort False
                              | TLRef True
                              | THead   False
                         that is equivalent to False
                         we proceed by induction on the previous result to prove ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                         we proved ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a

                         H5:eq T (TLRef i) (THead (Bind b) u t)
                           .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                case arity_abst : c0:C d:C u0:T i:nat :getl i c0 (CHead d (Bind Abst) u0) a:A :arity g d u0 (asucc g a) 
                   the thesis becomes 
                   H5:eq T (TLRef i) (THead (Bind b) u t)
                     .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                   () by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa1:A.arity g d u a1 λ:A.arity g (CHead d (Bind b) u) t (asucc g a)
                      suppose H5eq T (TLRef i) (THead (Bind b) u t)
                         (H6
                            we proceed by induction on H5 to prove 
                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef True
                                 | THead   False
                               case refl_equal : 
                                  the thesis becomes 
                                  <λ:T.Prop>
                                    CASE TLRef i OF
                                      TSort False
                                    | TLRef True
                                    | THead   False
                                     consider I
                                     we proved True

                                        <λ:T.Prop>
                                          CASE TLRef i OF
                                            TSort False
                                          | TLRef True
                                          | THead   False

                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef True
                                 | THead   False
                         end of H6
                         consider H6
                         we proved 
                            <λ:T.Prop>
                              CASE THead (Bind b) u t OF
                                TSort False
                              | TLRef True
                              | THead   False
                         that is equivalent to False
                         we proceed by induction on the previous result to prove ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                         we proved ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a

                         H5:eq T (TLRef i) (THead (Bind b) u t)
                           .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                case arity_bind : b0:B H2:not (eq B b0 Abst) c0:C u0:T a1:A H3:arity g c0 u0 a1 t0:T a0:A H5:arity g (CHead c0 (Bind b0) u0) t0 a0 
                   the thesis becomes 
                   H7:eq T (THead (Bind b0) u0 t0) (THead (Bind b) u t)
                     .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                   (H4) by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                   (H6) by induction hypothesis we know 
                      eq T t0 (THead (Bind b) u t)
                        (ex2
                             A
                             λa3:A.arity g (CHead c0 (Bind b0) u0) u a3
                             λ:A.arity g (CHead (CHead c0 (Bind b0) u0) (Bind b) u) t a0)
                      suppose H7eq T (THead (Bind b0) u0 t0) (THead (Bind b) u t)
                         (H8
                            by (f_equal . . . . . H7)
                            we proved 
                               eq
                                 B
                                 <λ:T.B>
                                   CASE THead (Bind b0) u0 t0 OF
                                     TSort b0
                                   | TLRef b0
                                   | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0
                                 <λ:T.B>
                                   CASE THead (Bind b) u t OF
                                     TSort b0
                                   | TLRef b0
                                   | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0

                               eq
                                 B
                                 λe:T
                                     .<λ:T.B>
                                       CASE e OF
                                         TSort b0
                                       | TLRef b0
                                       | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0
                                   THead (Bind b0) u0 t0
                                 λe:T
                                     .<λ:T.B>
                                       CASE e OF
                                         TSort b0
                                       | TLRef b0
                                       | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0
                                   THead (Bind b) u t
                         end of H8
                         (h1
                            (H9
                               by (f_equal . . . . . H7)
                               we proved 
                                  eq
                                    T
                                    <λ:T.T> CASE THead (Bind b0) u0 t0 OF TSort u0 | TLRef u0 | THead  t1 t1
                                    <λ:T.T> CASE THead (Bind b) u t OF TSort u0 | TLRef u0 | THead  t1 t1

                                  eq
                                    T
                                    λe:T.<λ:T.T> CASE e OF TSort u0 | TLRef u0 | THead  t1 t1 (THead (Bind b0) u0 t0)
                                    λe:T.<λ:T.T> CASE e OF TSort u0 | TLRef u0 | THead  t1 t1
                                      THead (Bind b) u t
                            end of H9
                            (h1
                               (H10
                                  by (f_equal . . . . . H7)
                                  we proved 
                                     eq
                                       T
                                       <λ:T.T> CASE THead (Bind b0) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                       <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1

                                     eq
                                       T
                                       λe:T.<λ:T.T> CASE e OF TSort t0 | TLRef t0 | THead   t1t1 (THead (Bind b0) u0 t0)
                                       λe:T.<λ:T.T> CASE e OF TSort t0 | TLRef t0 | THead   t1t1
                                         THead (Bind b) u t
                               end of H10
                                suppose H11eq T u0 u
                                suppose H12eq B b0 b
                                  (H13
                                     consider H10
                                     we proved 
                                        eq
                                          T
                                          <λ:T.T> CASE THead (Bind b0) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                          <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1
                                     that is equivalent to eq T t0 t
                                     we proceed by induction on the previous result to prove 
                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind b0) u0) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind b0) u0) (Bind b) u) t a0)
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H6

                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind b0) u0) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind b0) u0) (Bind b) u) t a0)
                                  end of H13
                                  (H14
                                     consider H10
                                     we proved 
                                        eq
                                          T
                                          <λ:T.T> CASE THead (Bind b0) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                          <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1
                                     that is equivalent to eq T t0 t
                                     we proceed by induction on the previous result to prove arity g (CHead c0 (Bind b0) u0) t a0
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H5
arity g (CHead c0 (Bind b0) u0) t a0
                                  end of H14
                                  (H15
                                     we proceed by induction on H11 to prove 
                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind b0) u) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind b0) u) (Bind b) u) t a0)
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H13

                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind b0) u) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind b0) u) (Bind b) u) t a0)
                                  end of H15
                                  (H16
                                     we proceed by induction on H11 to prove arity g (CHead c0 (Bind b0) u) t a0
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H14
arity g (CHead c0 (Bind b0) u) t a0
                                  end of H16
                                  (H18
                                     we proceed by induction on H11 to prove arity g c0 u a1
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H3
arity g c0 u a1
                                  end of H18
                                  (H20
                                     we proceed by induction on H12 to prove arity g (CHead c0 (Bind b) u) t a0
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H16
arity g (CHead c0 (Bind b) u) t a0
                                  end of H20
                                  by (ex_intro2 . . . . H18 H20)
                                  we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0

                                  eq T u0 u
                                    (eq B b0 b)(ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0)
                            end of h1
                            (h2
                               consider H9
                               we proved 
                                  eq
                                    T
                                    <λ:T.T> CASE THead (Bind b0) u0 t0 OF TSort u0 | TLRef u0 | THead  t1 t1
                                    <λ:T.T> CASE THead (Bind b) u t OF TSort u0 | TLRef u0 | THead  t1 t1
eq T u0 u
                            end of h2
                            by (h1 h2)

                               (eq B b0 b)(ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0)
                         end of h1
                         (h2
                            consider H8
                            we proved 
                               eq
                                 B
                                 <λ:T.B>
                                   CASE THead (Bind b0) u0 t0 OF
                                     TSort b0
                                   | TLRef b0
                                   | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0
                                 <λ:T.B>
                                   CASE THead (Bind b) u t OF
                                     TSort b0
                                   | TLRef b0
                                   | THead k  <λ:K.B> CASE k OF Bind b1b1 | Flat b0
eq B b0 b
                         end of h2
                         by (h1 h2)
                         we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0

                         H7:eq T (THead (Bind b0) u0 t0) (THead (Bind b) u t)
                           .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                case arity_head : c0:C u0:T a1:A H2:arity g c0 u0 (asucc g a1) t0:T a0:A H4:arity g (CHead c0 (Bind Abst) u0) t0 a0 
                   the thesis becomes 
                   H6:eq T (THead (Bind Abst) u0 t0) (THead (Bind b) u t)
                     .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)
                   (H3) by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (asucc g a1)
                   (H5) by induction hypothesis we know 
                      eq T t0 (THead (Bind b) u t)
                        (ex2
                             A
                             λa3:A.arity g (CHead c0 (Bind Abst) u0) u a3
                             λ:A.arity g (CHead (CHead c0 (Bind Abst) u0) (Bind b) u) t a0)
                      suppose H6eq T (THead (Bind Abst) u0 t0) (THead (Bind b) u t)
                         (H7
                            by (f_equal . . . . . H6)
                            we proved 
                               eq
                                 B
                                 <λ:T.B>
                                   CASE THead (Bind Abst) u0 t0 OF
                                     TSort Abst
                                   | TLRef Abst
                                   | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst
                                 <λ:T.B>
                                   CASE THead (Bind b) u t OF
                                     TSort Abst
                                   | TLRef Abst
                                   | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst

                               eq
                                 B
                                 λe:T
                                     .<λ:T.B>
                                       CASE e OF
                                         TSort Abst
                                       | TLRef Abst
                                       | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst
                                   THead (Bind Abst) u0 t0
                                 λe:T
                                     .<λ:T.B>
                                       CASE e OF
                                         TSort Abst
                                       | TLRef Abst
                                       | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst
                                   THead (Bind b) u t
                         end of H7
                         (h1
                            (H8
                               by (f_equal . . . . . H6)
                               we proved 
                                  eq
                                    T
                                    <λ:T.T> CASE THead (Bind Abst) u0 t0 OF TSort u0 | TLRef u0 | THead  t1 t1
                                    <λ:T.T> CASE THead (Bind b) u t OF TSort u0 | TLRef u0 | THead  t1 t1

                                  eq
                                    T
                                    λe:T.<λ:T.T> CASE e OF TSort u0 | TLRef u0 | THead  t1 t1
                                      THead (Bind Abst) u0 t0
                                    λe:T.<λ:T.T> CASE e OF TSort u0 | TLRef u0 | THead  t1 t1
                                      THead (Bind b) u t
                            end of H8
                            (h1
                               (H9
                                  by (f_equal . . . . . H6)
                                  we proved 
                                     eq
                                       T
                                       <λ:T.T> CASE THead (Bind Abst) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                       <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1

                                     eq
                                       T
                                       λe:T.<λ:T.T> CASE e OF TSort t0 | TLRef t0 | THead   t1t1
                                         THead (Bind Abst) u0 t0
                                       λe:T.<λ:T.T> CASE e OF TSort t0 | TLRef t0 | THead   t1t1
                                         THead (Bind b) u t
                               end of H9
                                suppose H10eq T u0 u
                                suppose H11eq B Abst b
                                  (H12
                                     consider H9
                                     we proved 
                                        eq
                                          T
                                          <λ:T.T> CASE THead (Bind Abst) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                          <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1
                                     that is equivalent to eq T t0 t
                                     we proceed by induction on the previous result to prove 
                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind Abst) u0) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind Abst) u0) (Bind b) u) t a0)
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H5

                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind Abst) u0) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind Abst) u0) (Bind b) u) t a0)
                                  end of H12
                                  (H13
                                     consider H9
                                     we proved 
                                        eq
                                          T
                                          <λ:T.T> CASE THead (Bind Abst) u0 t0 OF TSort t0 | TLRef t0 | THead   t1t1
                                          <λ:T.T> CASE THead (Bind b) u t OF TSort t0 | TLRef t0 | THead   t1t1
                                     that is equivalent to eq T t0 t
                                     we proceed by induction on the previous result to prove arity g (CHead c0 (Bind Abst) u0) t a0
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H4
arity g (CHead c0 (Bind Abst) u0) t a0
                                  end of H13
                                  (H14
                                     we proceed by induction on H10 to prove 
                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind Abst) u) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind Abst) u) (Bind b) u) t a0)
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H12

                                        eq T t (THead (Bind b) u t)
                                          (ex2
                                               A
                                               λa3:A.arity g (CHead c0 (Bind Abst) u) u a3
                                               λ:A.arity g (CHead (CHead c0 (Bind Abst) u) (Bind b) u) t a0)
                                  end of H14
                                  (H16
                                     we proceed by induction on H10 to prove 
                                        eq T u (THead (Bind b) u t)
                                          ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (asucc g a1)
                                        case refl_equal : 
                                           the thesis becomes the hypothesis H3

                                        eq T u (THead (Bind b) u t)
                                          ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (asucc g a1)
                                  end of H16
                                  (H20
                                     by (eq_ind_r . . . H . H11)
not (eq B Abst Abst)
                                  end of H20
                                  we proceed by induction on H11 to prove ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)
                                     case refl_equal : 
                                        the thesis becomes ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind Abst) u) t (AHead a1 a0)
                                           (H21
                                              by (refl_equal . .)
                                              we proved eq B Abst Abst
                                              by (H20 previous)
                                              we proved False
                                              by cases on the previous result we prove ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind Abst) u) t (AHead a1 a0)
ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind Abst) u) t (AHead a1 a0)
                                           end of H21
                                           consider H21
ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind Abst) u) t (AHead a1 a0)
                                  we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)

                                  eq T u0 u
                                    (eq B Abst b
                                         ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0))
                            end of h1
                            (h2
                               consider H8
                               we proved 
                                  eq
                                    T
                                    <λ:T.T> CASE THead (Bind Abst) u0 t0 OF TSort u0 | TLRef u0 | THead  t1 t1
                                    <λ:T.T> CASE THead (Bind b) u t OF TSort u0 | TLRef u0 | THead  t1 t1
eq T u0 u
                            end of h2
                            by (h1 h2)

                               eq B Abst b
                                 ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)
                         end of h1
                         (h2
                            consider H7
                            we proved 
                               eq
                                 B
                                 <λ:T.B>
                                   CASE THead (Bind Abst) u0 t0 OF
                                     TSort Abst
                                   | TLRef Abst
                                   | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst
                                 <λ:T.B>
                                   CASE THead (Bind b) u t OF
                                     TSort Abst
                                   | TLRef Abst
                                   | THead k  <λ:K.B> CASE k OF Bind b0b0 | Flat Abst
eq B Abst b
                         end of h2
                         by (h1 h2)
                         we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)

                         H6:eq T (THead (Bind Abst) u0 t0) (THead (Bind b) u t)
                           .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)
                case arity_appl : c0:C u0:T a1:A :arity g c0 u0 a1 t0:T a0:A :arity g c0 t0 (AHead a1 a0) 
                   the thesis becomes 
                   H6:eq T (THead (Flat Appl) u0 t0) (THead (Bind b) u t)
                     .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                   () by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                   () by induction hypothesis we know 
                      eq T t0 (THead (Bind b) u t)
                        ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t (AHead a1 a0)
                      suppose H6eq T (THead (Flat Appl) u0 t0) (THead (Bind b) u t)
                         (H7
                            we proceed by induction on H6 to prove 
                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef False
                                 | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                               case refl_equal : 
                                  the thesis becomes 
                                  <λ:T.Prop>
                                    CASE THead (Flat Appl) u0 t0 OF
                                      TSort False
                                    | TLRef False
                                    | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                                     consider I
                                     we proved True

                                        <λ:T.Prop>
                                          CASE THead (Flat Appl) u0 t0 OF
                                            TSort False
                                          | TLRef False
                                          | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True

                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef False
                                 | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                         end of H7
                         consider H7
                         we proved 
                            <λ:T.Prop>
                              CASE THead (Bind b) u t OF
                                TSort False
                              | TLRef False
                              | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                         that is equivalent to False
                         we proceed by induction on the previous result to prove ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                         we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0

                         H6:eq T (THead (Flat Appl) u0 t0) (THead (Bind b) u t)
                           .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                case arity_cast : c0:C u0:T a:A :arity g c0 u0 (asucc g a) t0:T :arity g c0 t0 a 
                   the thesis becomes 
                   H6:eq T (THead (Flat Cast) u0 t0) (THead (Bind b) u t)
                     .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                   () by induction hypothesis we know 
                      eq T u0 (THead (Bind b) u t)
                        ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t (asucc g a)
                   () by induction hypothesis we know 
                      eq T t0 (THead (Bind b) u t)
                        ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                      suppose H6eq T (THead (Flat Cast) u0 t0) (THead (Bind b) u t)
                         (H7
                            we proceed by induction on H6 to prove 
                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef False
                                 | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                               case refl_equal : 
                                  the thesis becomes 
                                  <λ:T.Prop>
                                    CASE THead (Flat Cast) u0 t0 OF
                                      TSort False
                                    | TLRef False
                                    | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                                     consider I
                                     we proved True

                                        <λ:T.Prop>
                                          CASE THead (Flat Cast) u0 t0 OF
                                            TSort False
                                          | TLRef False
                                          | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True

                               <λ:T.Prop>
                                 CASE THead (Bind b) u t OF
                                   TSort False
                                 | TLRef False
                                 | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                         end of H7
                         consider H7
                         we proved 
                            <λ:T.Prop>
                              CASE THead (Bind b) u t OF
                                TSort False
                              | TLRef False
                              | THead k  <λ:K.Prop> CASE k OF Bind False | Flat True
                         that is equivalent to False
                         we proceed by induction on the previous result to prove ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                         we proved ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a

                         H6:eq T (THead (Flat Cast) u0 t0) (THead (Bind b) u t)
                           .ex2 A λa1:A.arity g c0 u a1 λ:A.arity g (CHead c0 (Bind b) u) t a
                case arity_repl : c0:C t0:T a1:A H2:arity g c0 t0 a1 a0:A H4:leq g a1 a0 
                   the thesis becomes 
                   H5:eq T t0 (THead (Bind b) u t)
                     .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                   (H3) by induction hypothesis we know 
                      eq T t0 (THead (Bind b) u t)
                        ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                      suppose H5eq T t0 (THead (Bind b) u t)
                         (H6
                            by (f_equal . . . . . H5)
                            we proved eq T t0 (THead (Bind b) u t)
eq T (λe:T.e t0) (λe:T.e (THead (Bind b) u t))
                         end of H6
                         (H7
                            we proceed by induction on H6 to prove 
                               eq T (THead (Bind b) u t) (THead (Bind b) u t)
                                 ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                               case refl_equal : 
                                  the thesis becomes the hypothesis H3

                               eq T (THead (Bind b) u t) (THead (Bind b) u t)
                                 ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                         end of H7
                         (H9
                            by (refl_equal . .)
                            we proved eq T (THead (Bind b) u t) (THead (Bind b) u t)
                            by (H7 previous)
ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a1
                         end of H9
                         we proceed by induction on H9 to prove ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                            case ex_intro2 : x:A H10:arity g c0 u x H11:arity g (CHead c0 (Bind b) u) t a1 
                               the thesis becomes ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                                  by (arity_repl . . . . H11 . H4)
                                  we proved arity g (CHead c0 (Bind b) u) t a0
                                  by (ex_intro2 . . . . H10 previous)
ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
                         we proved ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0

                         H5:eq T t0 (THead (Bind b) u t)
                           .ex2 A λa3:A.arity g c0 u a3 λ:A.arity g (CHead c0 (Bind b) u) t a0
             we proved 
                eq T y (THead (Bind b) u t)
                  ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2
          we proved 
             y:T
               .arity g c y a2
                 (eq T y (THead (Bind b) u t)
                      ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2)
          by (insert_eq . . . . previous H0)
          we proved ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2
       we proved 
          b:B
            .not (eq B b Abst)
              g:G
                   .c:C
                     .u:T
                       .t:T
                         .a2:A
                           .arity g c (THead (Bind b) u t) a2
                             ex2 A λa1:A.arity g c u a1 λ:A.arity g (CHead c (Bind b) u) t a2